PENGARUH HARGA, PROMOSI DAN MEREK TERHADAP KEPUASAN KONSUMEN MENGGUNAKAN SKIN CARE HIMALAYA PADA PT. THE HIMALAYA DRUG COMPANY DI MEDAN - Fenny Krisna Marpaung; Marisi Anastasia Samosir; Enda Ferbina; Lusiana Girsang; Irma Ndraha (JURNAL MANAJEMEN, 2020)
The purpose of this study was to determine the effect of price, promotion and brand on consumer decisions using Himalayan skin care at PT. The Himalaya Drug Company Medan. This research method is a quantitative approach research that focuses on symptoms that have certain characteristics in human life which are called variables. The population in this study were 122 employees of PT. Himalaya Drug Company Medan. Primary data will use questionnaires, interviews, and secondary data. The results of the study based on the F test showed that the results of Fcount > Ftable (34.409> 3.07) showed that the independent variables of price, promotion and brand simultaneously had a positive and significant effect on the dependent variable of consumer satisfaction. Partially (t-test) shows that price, promotion and brand have a positive and significant effect on customer satisfaction. Adjusted R Square (R2) 45.3% of the consumer satisfaction variable could be explained by price, promotion and brand variables, while 54.7% could be explained by other variables not examined in this study.